Sociology and visual representation - Chaplin, Elizabeth 1939- (London Routledge, 1994)
Our culture has become far more visual. Recent technological developments have engendered a transformation. Visual representation now concerns a wide spectrum of social scientists: no longer is it the province of a mere handful interested in visual art. This book is concerned with still images, diagrams, and the visual presentation of the written text. It is particularly aimed at postgraduate students, and provides a selective historical survey of texts whose authors have contributed to the development of the social analysis of visual representation. It focuses, especially, on those recent texts which have changed the relationship of analysis to topic by incorporating visual representation into the analysis itself.
The first section of the book focuses on 'critical' accounts. It charts the history of critical theories and critical analyses of visual art from the propositions of antiquity to the present day. The author shows that photography, critical post-modernism and, above all, feminism have each played a part in blurring the distinction between art and non-art visual representations and in questioning the assumption that the verbal does the analysing while the visual merely constitutes the object of analysis. Chaplin argues that critical analyses of society are powerful when both verbal and visual dimensions are consciously activated and coordinated. The second section charts the history of empirical social analyses of visual art, scientific and other depictions. Again, it highlights those works that make use of the visual dimension, especially in the field of anthropology; and it includes an account of Elizabeth Chaplin's own photographic project.
The section ends by examining social science accounts which take new literary forms, for these indicate that attention to the visual dimension of textual presentation reaches to the heart of current methodological issues. Chaplin demonstrates that while depictions can contribute to social science analysis things that words alone cannot, unconventional typography and page layout can also add sociological meaning and contribute to a sound methodological stance. She urges social scientists to make more conscious use of visual representation in their analyses. And she suggests that such a course offers social scientists who are women the opportunity to develop a distinctive women's approach to social analysis.
1. Critical writing about visual art. 1. Introduction and early writings. 2. Critical writings about visual art: class analyses I. 3. Non-critical writings about visual art: connoisseurship, humanism. 4. Critical writings about visual art: class analyses II -- 2. From written, class analyses of visual art to the use of visual representation in critique -- 3. Visual and verbal critique: feminism and postmodernism -- 4. Sociological analyses of visual representation -- 5. The use of visual representation in anthropology and sociology -- 6. Visual representation and new literary forms for sociology -- 7. A coming together.
Includes bibliographical references (pages [284]-294) and indexes.
Keywords: Art and society -- History -- 20th century; Visual communication